The lure of Pokémon - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
"Video games are often thought to draw children out of nature and into isolated, closed spaces. In The Lure of Pokémon: Video Games and the Savage Mind, however, Nakazawa Shinichi shows how the Pokémon series of video games, far from standing in opposition to nature, actually seeks to represent the true, hidden essence of the natural world. From humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the real world with "augmented reality" via the mobile game Pokémon Go